Knowledge and perception of medical students regarding remote-access thyroidectomy in Tabuk: the effects of extensive counseling—an interventional study - Mirghani, Hyder; Alhowiti, Amirah (Frontiers in Surgery, 2024)
IntroductionRemote-access scarless thyroidectomies are relatively new surgical procedures, and their uptake for cosmetic concerns is rapidly evolving. However, demographic factors, previous thyroid surgery, and culture substantially influence the patient's choice. This is the first study to assess the extensive counseling effect on the patient's preference for remote-access thyroidectomies compared to conventional transcervical approaches. We aimed to assess the same among medical students at the University of Tabuk, Saudi Arabia.MethodsThis interventional study was conducted from December 2023 to March 2024. A structured questionnaire was used to gather information about demographic factors, knowledge, and perception of the medical students regarding remote-access thyroidectomies before and after a slide presentation.ResultsOf 394 medical students (age 22.65 ± 1.62 years), 53.8% were women. Initially, the majority of the students preferred remote-access thyroidectomy over the conventional approach (85.3% vs. 14.7%, respectively); however, a substantial change toward the cervical approach was evident after extensive counseling [odds ratio, 2.59; 95% confidence interval (CI), 1.58–4.27; and P-value <0.00]. Knowledge regarding remote-access thyroidectomy was poor (26.9%). The students were anxious regarding postoperative complications (3.22 ± 1.59/5), thyroid scar appearance (3.28 ± 1.36/5), and postoperative pain (3.17 ± 1.38/5). Concerns regarding body satisfaction and cost were lower.ConclusionMedical students at the University of Tabuk, Saudi Arabia, demonstrated low knowledge. The strong preference for remote-access thyroidectomy over transcervical thyroidectomy shifted substantially toward the conventional approach after counseling. The main factors were thyroid scar appearance, pain, and complications. Further larger-scale studies involving the general public and assessing the effect of extensive counseling on surgical choice are needed.